Training in Nursing for management practice: integrative review (Research, Society and Development, 2021)
Objective: Identify in the scientific evidence the themes addressed about the practice of management in nursing education. Methodology: Integrative literature review, with data collection in September 2021, in the following databases: Pubmed, LILACS (Latin American and Caribbean Literature on Health Sciences) and BDEnf. Results: Of a total of 6 articles, all were carried out in Brazil, from textual analysis, we discuss themes such as: formation and needs of the SUS, permanent education and the need to train nurses for the area, curriculum subjects, methodology, theory and practice and nursing for management. Conclusions: The study verified the difficulties in the approximation/link between higher education institutions and health services, enabled the discovery of the field diary as a positive tool in the learning process and it was confirmed that practical activities, as well as in other themes, are seen as essential for the management experience.